2020
DOI: 10.1177/1947603520951631
|View full text |Cite
|
Sign up to set email alerts
|

Pondering the Potential of Hyaline Cartilage–Derived Chondroprogenitors for Tissue Regeneration: A Systematic Review

Abstract: Objective Chondroprogenitors have recently gained prominence due to promising results seen in in vitro and animal studies as a potential contender in cell-based therapy for cartilage repair. Lack of consensus regarding nomenclature, isolation techniques, and expansion protocols create substantial limitations for translational research, especially given the absence of distinct markers of identification. The objective of this systematic review was to identify and collate information pertaining to hyaline cartila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 76 publications
0
16
0
4
Order By: Relevance
“…180,181 As chondrocytes also exhibit favorable properties for cartilage repair, there are systematic reviews that have collated information on the culture and expansion capability of chondrocytes; highlighting that chondrogenic phenotype can be maintained using low glucose and hypoxic conditions. 182 63,176 In vivo chondrocytes demonstrated the potential for long-term survival of transplanted cells; transplanted autologous auricular chondrocytes were shown to survive for at least 6 months in a rabbit model, 178 and porcine articular cartilage remained viable at 12 months post injection into a porcine model. 184 ‡ ‡ ‡ ‡ Throughout the studies using chondrocytes for cell therapy for IVD regeneration, the cells were shown to be tolerant to the IVD environment, most probably due to its similarities to the condition of cartilage the chondrocytes are derived, and remain viable post-transplantation in small animal models.…”
Section: Discussionmentioning
confidence: 99%
“…180,181 As chondrocytes also exhibit favorable properties for cartilage repair, there are systematic reviews that have collated information on the culture and expansion capability of chondrocytes; highlighting that chondrogenic phenotype can be maintained using low glucose and hypoxic conditions. 182 63,176 In vivo chondrocytes demonstrated the potential for long-term survival of transplanted cells; transplanted autologous auricular chondrocytes were shown to survive for at least 6 months in a rabbit model, 178 and porcine articular cartilage remained viable at 12 months post injection into a porcine model. 184 ‡ ‡ ‡ ‡ Throughout the studies using chondrocytes for cell therapy for IVD regeneration, the cells were shown to be tolerant to the IVD environment, most probably due to its similarities to the condition of cartilage the chondrocytes are derived, and remain viable post-transplantation in small animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Though a multitude of reports using cell-based therapy has demonstrated therapeutic efficiency, the ensuing fibrocartilage tissue tends to be a poor substitute for long-term subsistence 39 . The discovery of cartilage resident progenitors, displaying superior chondrogenic potential and lower hypertrophic tendencies, has led to the evaluation of their use for tissue engineering applications 23 . However, clarification of their biological properties is warranted before their therapeutic use can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Both fibronectin adhesion assay derived 19 , 20 and migratory chondroprogenitors 8 , 21 have been likened to MSCs as delineated by the International Society for Cellular Therapy (ISCT) 2006 22 , demonstrating plastic adherence, similar surface marker expression, and trilineage differentiation potential. Extensive work on these progenitors has provided information on their growth characteristics, where fibronectin-derived cells displayed clonal growth and required additional growth factors for expansion, unlike migratory progenitors 23 . As compared to bone marrow-MSCs, independent in- vivo animal studies using these progenitors show that they are more effective in repairing chondral defects 11 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] To optimize the use of chondroprogenitors, numerous techniques for isolation based on migratory ability, selective adhesion to fibronectin, and specific cell surface marker profile have been studied. 11 The fibronectin differential adhesion assay, a commonly employed technique for isolation of chondroprogenitors, has repeatedly yielded cells demonstrating superiority for chondrogenesis. Some characteristics of the chondroprogenitors include differential adhesion to fibronectin, 2,12 differential expression of integrins and Notch proteins, 13,14 and high replicative potential, with the ability to form large number of colonies even with low seeding density.…”
Section: Introductionmentioning
confidence: 99%